Indirect Disaster-Related Death Associated With Cognitive Decline Among Older People Following Evacuation During A Radiation Disaster: A Case Report - Yamamoto, Chika; Sawano, Toyoaki; Ozaki, Akihiko; Fuji, Kenta; Ito, Naomi; Yamamura, Momoka; Hori, Arinobu; Zhao, Tianchen; Tsubokura, Masaharu (Universitas Gadjah Mada, 2025)
Introduction: During disasters, older adults are vulnerable to indirect health effects caused by evacuation-related environmental changes. Despite existing reports of depression and cognitive decline in this population, detailed case-based analyses during prolonged evacuations following radiation disasters remain limited. Objective: This case study aims to examine the impact of evacuation on cognitive function and subsequent health decline in an older adult. Methods: We analyzed medical records, evacuation documents, and semi-structured interviews with the bereaved family. These sources were integrated and chronologically organized to assess the health impact of prolonged displacement. Results: An 88-year-old man, evacuated following the Fukushima Daiichi Nuclear Power Plant accident, experienced initial delirium, a temporary recovery upon returning home, and a relapse upon re-evacuation. Continuous displacement and repeated environmental changes led to progressive cognitive and physical decline, ultimately resulting in a disaster-related death. Conclusions: This case illustrates that evacuation during disasters can have serious impacts on the cognitive function and overall health of older adults. In particular, older individuals who are at risk of cognitive decline should be promptly relocated to evacuation sites where they can receive immediate and continuous medical and social support. Such measures are essential for mitigating health risks among older populations in future disasters.